The atypical mitogen-activated protein kinase ERK3 is essential for establishment of epithelial architecture - Takahashi, Chika (J Biol Chem, 2018)
Epithelia contribute to physical barriers that protect internal tissues from the external environment and also support organ structure. Accordingly, establishment and maintenance of epithelial architecture are essential for both embryonic development and adult physiology. Here, using gene knockout and knockdown techniques along with gene profiling, we show that extracellular signal–regulated kinase 3 (ERK3), a poorly characterized atypical mitogen-activated protein kinase (MAPK), regulates the epithelial architecture in vertebrates. We found that in Xenopus embryonic epidermal epithelia, ERK3 knockdown impairs adherens and tight-junction protein distribution, as well as tight-junction barrier function, resulting in epidermal breakdown. Moreover, in human epithelial breast cancer cells, inhibition of ERK3 expression induced thickened epithelia with aberrant adherens and tight junctions. Results from microarray analyses suggested that transcription factor AP-2α (TFAP2A), a transcriptional regulator important for epithelial gene expression, is involved in ERK3-dependent changes in gene expression. Of note, TFAP2A knockdown phenocopied ERK3 knockdown in both Xenopus embryos and human cells, and ERK3 was required for full activation of TFAP2A-dependent transcription. Our findings reveal that ERK3 regulates epithelial architecture, possibly together with TFAP2A.